Screening of Extracts of Leaves and Stems of Psychotria spp. (Rubiaceae) against Sitophilus zeamais (Coleoptera: Curculionidae) and Spodoptera frugiperda (Lepidoptera: Noctuidae) for Maize Protection - Tavares, Wagner de Souza; Grazziotti, Geisel Hudson; Souza Junior, Amauri Alves de [UNESP]; Freitas, Silvia de Sousa; Consolaro, Helder Nagai; Aquino Ribeiro, Paulo Eduardo de; Zanuncio, Jose Cola (Int Assoc Food Protection, 2013)
Sitophilus zeamais (Coleoptera: Curculionidae) and Spodoptera frugiperda (Lepidoptera: Noctuidae) are important economic pests of corn, Zea mays (Poaceae). Psychotria spp. (Rubiaceae) plants are rich in secondary metabolites that could be toxic against such pests. We have screened extracts from four species of Psychotria abundant in the Cerrado (Savannah-type) biome of Brazil for the toxicity to two insects. We found that extracts from leaves and stems had significant effects on the hatching rate, parameters of caterpillar body (weight and length and width of head capsule), repellency, and mortality of these two pests, although the effects varied according to the Psychotria species and plant source (stem or leaf). Extracts of the stems of Psychotria hoffmannseggiana and of Psychotria capitata were more toxic to S. zeamais and the stems of Psychotria goyazensis to S. frugiperda; therefore, such extracts could have the potential for use in integrated pest management schemes.